An idea of the test stand for studies of magnetobarocaloric materials properties and possibilities of their application. Issue 5 (31st March 2014) - Czernuszewicz, A.; Kaleta, J.; Lewandowski, D.; Przybylski, M.
Abstract: The paper presents an idea of the laboratory test stand for evaluation of the application potential of magnetobarocaloric materials. These materials are characterized by the temperature change under stimulation by a magnetic field and mechanical loading. This property of the material can be used for construction of cooling and heating devices. Thanks to the ecofriendly character of the solutions based on this material it may replace, in the near future, nowadays solutions based on the gas compression–decompression method. The presented laboratory test stand will allow comparison of the several groups of materials in terms of their application in modern cooling systems. The paper shows the main ideas behind the construction and working principles of the system. To obtain a change in the temperature of the tested material it will be subjected to the magnetic field generated by permanent magnets and mechanical loading generated with use of a universal testing machine. Loading will cause a uniaxial tension state in the material. Magnetobarocaloric material, working as a refrigerant in the device, will be applied as a multiflow system. The test stand will work in a modified active magnetic regenerator (AMR) cycle that is most commonly used in prototypes of magnetic refrigerators. This cycle will be adapted for the use of mechanical loading in addition to magnetic stimulation. The test stand presented in this paper is currently under construction. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)